Gambaran Nilai Darah Pada Sapi Yang Terinfeksi Fascioliasis Yang Dipotong di Rumah Potong Hewan Kota Banda Aceh - Winaruddin Winaruddin (Jurnal Agripet, 2002)
ABSTRACT.The main purpose of the research was to determain the blood value of fascioliasis on blood of the cattle slaughtered in abattoir. It has been examined fifty samples of fecal, bile fluids and blood of the cattle slaughtered at the Banda Aceh abattoir. The samples were examined for the values of hematocrit, erythrocyte and leucocyte differentiation and the presence of helminth eggs respectively. It was found that the egg count variet from 7.168 0.225 trematode eggs in fecal samples and 14.554 2.154 trematode eggs in bile duct repectively. The result of this study showed that, the prevalence rate of fascioliasis in cattle categorical a mild infestation was 44 %. Both in the length and width of body size of the flukes are affected by the life stage. The size of adult fluke was about 34.649 8.992 mm x 12.030 3.494 mm, while that of young fluke was 1.650 0.240 mm x 1.487 0.227 mm. the blood indices of affected cattle indicated significant (P 0.05) decrease in hematocrit and erythrocyte count compared with those not affected by the disease. The mean count of hematocrit and erythrocyte 29.773% 3.366% and 547.337 x 104 13.599 in cattle infected and in cattle non infected was 32.357 2.818 and 566.457 x 104 12.886 respectively. The result of this study, also significant (P 0.05) in increasing of the eosinophilia 16.22% 4.03% compared with that non-affected ones (10.54 4.56).